2020
DOI: 10.1177/2325967120908884
|View full text |Cite
|
Sign up to set email alerts
|

CrossFit and the Epidemiology of Musculoskeletal Injuries: A Prospective 12-Week Cohort Study

Abstract: Background: Despite the increasing international popularity of CrossFit, there is a paucity of scientific evidence on the risk of CrossFit-related musculoskeletal injuries (CRMIs). Purpose: To investigate the incidence (cumulative incidence proportion [IP] and incidence density [ID]) of CRMIs and the association of CRMIs with personal and training characteristics. Study Design: Descriptive epidemiology study. Methods: A prospective, 12-week descriptive epidemiology cohort study was conducted in a convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 37 publications
4
62
1
6
Order By: Relevance
“…A similar study conducted in Brazil had a similar finding in that before quarantine, muscle injuries accounted for 45.4% of injuries, while bruises only accounted for 5.3% [20]. A different study reported that joint injuries (43.6%) comprised the majority of injuries, followed by muscle strains (27.7%), making bruises (26.7%) the third most common form of injury [21]. A study in Portuguese found that most injuries were joint injuries (30.8%), followed by muscle strains (23.1%) [22].…”
Section: Discussionsupporting
confidence: 54%
“…A similar study conducted in Brazil had a similar finding in that before quarantine, muscle injuries accounted for 45.4% of injuries, while bruises only accounted for 5.3% [20]. A different study reported that joint injuries (43.6%) comprised the majority of injuries, followed by muscle strains (27.7%), making bruises (26.7%) the third most common form of injury [21]. A study in Portuguese found that most injuries were joint injuries (30.8%), followed by muscle strains (23.1%) [22].…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have reported that a history of previous injuries would increase the risk of reinjury. 13 , 34 This association can be explained by a change in strength, proprioception, and kinematics in the injured state, which may lead to changes in motor control and function. 10 Maximal effort in SW freestyle and bodyweight exercises may be a challenge for practitioners, especially those injured before and not fully recovered.…”
Section: Discussionmentioning
confidence: 99%
“…As causas mais atribuídas de lesão foram a forma inadequada (33,3%) e exacerbação de lesão anterior (33,3%). Vinte e cinco (64,1%) daqueles que sofreram lesão relataram 1 mês ou menos de redução de treinamento devido ao ferimento Acerca do estabelecimento de uma taxa de injúria, o estudo prospecGvo de coorte [68] realizou 406 quesGonários efeGvos para invesGgar a incidência de injúrias musculoesqueléGca que prevenia o atleta de se exercitar por no mínimo 1 dia, o que classificaram como CRMI. Encontraram que 32% dos atletas relataram essas injúrias e foi encontrado que a taxa de injúria, a cada 1000h de exposição de treino equivalia a 18,9.…”
Section: Tabelaunclassified